Analysis of social research methodologies on gender relations in Agriculture, Fisheries and Forestry (2000)
The paper reviewed 52 empirical studies on gender in agriculture, fisheries and forestry. These were local studies between 1980 and 1999 which had an explicit description of the research methods used. The aim of the review was to examine the methods used by analyzing their epistemological bases in the context of sustainable development. Most of the studies reviewed utilized the survey method based on a nomothetic epistemology. These studies showed the different roles of women and men in production and processing aspects of agriculture, fisheries and forestry. A few studies used qualitative methods with very little attempt to get at the subjective meanings of different activities for women and men in the situations and development projects studied as required by an interpretive epistemology. Some studies analyzed gender based participation in development projects and the impacts of different technologies implying the instrumental nature of such projects both in improving the living conditions of households and in promoting sustainable development. These studies comprise an initial step toward a bigger stride for transformational epistemology. The paper concludes by advocating a greater complementation of research methods based on different epistemologies in the study of gender relations in agriculture, fisheries and forestry
Keywords: Sustainable development; Theory of knowledge